Tin-phosphor bronze alloy strip and preparation method thereof

By controlling the grain size and grain boundary structure of the tin-phosphor bronze alloy strip and combining with specific preparation technology, the problem that existing tin-phosphor bronze alloys are difficult to have high mechanical strength and high bending properties is solved, and high strength and hardness are achieved And excellent bending performance, meet the miniaturization needs of electronic components.

CN116121585BActive Publication Date: 2025-02-14CHINALCO RES INST OF SCI & TECH CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211103029.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-02-14
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

The existing tin-phosphor bronze alloys are difficult to meet the needs of high mechanical strength and high bending at the same time, and it is difficult to support the miniaturization of electronic components and the miniaturization and thinner structural design of connectors.

Method used

By controlling the average grain size of the tin-phosphor bronze alloy strip less than 2μm, the grains show a normal distribution with a standard deviation of less than 0.9μm, and the proportion of large-angle grain boundaries and total low ΣCSL grain boundaries is increased, combined with specific preparation The process flow, including multiple heat treatments and cold rolling, optimizes the distribution of texture components.

Benefits of technology

It realizes the high strength, hardness and toughness of the tin-phosphorus bronze alloy strip, and shows excellent bending performance in bending processing. It can take into account tensile strength and bending performance to meet the needs of miniaturization and thinning of the connector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121585B_ABST
    Figure CN116121585B_ABST
Patent Text Reader

Abstract

The present invention provides a tin-phosphor bronze alloy strip and a preparation method thereof. In terms of mass percentage, the tin-phosphor bronze alloy strip comprises: 4.0-10wt% Sn, 0.01-0.3wt% P, and the remainder is Cu and unavoidable impurity elements. The average grain size of the tin-phosphor bronze alloy strip is less than 2μm, and the grains are normally distributed with a standard deviation of less than 0.9μm. The total low ΣCSL grain boundaries in the tin-phosphor bronze alloy strip account for 10-45% of the entire grain boundaries, the length fraction of the high-angle grain boundaries in the tin-phosphor bronze alloy strip is 40-85%, and the length fraction of the low-angle grain boundaries is 15-60%. The tin-phosphor bronze alloy strip has excellent bending performance in the BW direction, and no defects such as wrinkles occur at a lower R / t value in the BW direction, and the tin-phosphor bronze alloy strip can take into account both excellent tensile strength and excellent bending performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tin-phosphor bronze alloys, and in particular to a tin-phosphor bronze alloy strip and a preparation method thereof. Background Art

[0002] Tin-phosphor bronze is a commonly used elastic copper alloy. It can obtain good mechanical properties through the action of Sn and P elements and cold working hardening. It is easy to process and punch into elastic components of various complex shapes. It not only has excellent elastic properties, but also has the characteristics of corrosion resistance, wear resistance and non-magneticity. It is currently the most widely used and most widely used elastic material among copper-based elastic alloy materials. However, with the rapid development of science and technology, electronic components are developing in the direction of miniaturization, and the components used in terminal connectors are also developing in the direction of miniaturization, making the bending radius of the components smaller, and the bending processing of the components is more prone to wrinkles, orange peel and cracks. This requires that the tin-phosphor bronze widely used in terminal connectors has higher bendability and high mechanical strength to meet the growing needs of electronic components. However, ordinary tin-phosphor bronze alloys can no longer meet the above performance requirements at the same time, and it is difficult to support the needs of miniaturization and thin structure design of connectors. Summary of the invention

[0003] The main purpose of the present invention is to provide a tin-phosphor bronze alloy strip and a preparation method thereof, so as to solve the problem in the prior art that the tin-phosphor bronze alloy is difficult to have both high mechanical strength and high bendability.

[0004] To achieve the above-mentioned object, according to one aspect of the present invention, a tin-phosphorus bronze alloy strip is provided, which comprises, by mass percentage, 4.0-10wt% Sn, 0.01-0.3wt% P, and the remainder is Cu and unavoidable impurity elements, the average grain size of the tin-phosphorus bronze alloy strip is less than 2μm, the grains are normally distributed, and the standard deviation is less than 0.9μm; the total low ΣCSL grain boundaries in the tin-phosphorus bronze alloy strip account for 10-45% of the entire grain boundaries, the length fraction of the high-angle grain boundaries in the tin-phosphorus bronze alloy strip is 40-85%, and the length fraction of the low-angle grain boundaries is 15-60%.

[0005] Furthermore, the ratio of the length fraction of the high-angle grain boundary to the length fraction of the low-angle grain boundary is 1.38-5.67:1, preferably any one or more of 1.38-1.86:1, 2.33-2.57:1, and 3.55-5.67:1.

[0006] Furthermore, the texture components in the above-mentioned tin-phosphorus bronze alloy strip include: a Gaussian texture with an area fraction of 3-8%, a copper-type texture with an area fraction of 1-3%, and a brass-type texture with an area fraction of 3-6%; and the texture components are randomly distributed.

[0007] Furthermore, the tensile strength of the tin-phosphorus bronze alloy strip is 610-1000 MPa, the yield strength of the tin-phosphorus bronze alloy strip is preferably 580-980 MPa, the elongation of the tin-phosphorus bronze alloy strip is preferably 10-35%, and the hardness of the tin-phosphorus bronze alloy strip is preferably 200-286 HV.

[0008] Furthermore, when the tin-phosphor bronze alloy strip is bent at 90°, the R / t value in the GW direction is 0, and the R / t value in the BW direction is ≤0.5.

[0009] According to another aspect of the present invention, a method for preparing the above-mentioned tin-phosphorus bronze alloy strip is provided, and the preparation process of the tin-phosphorus bronze alloy strip comprises a batching step, a horizontal continuous casting step, a pre-rolling step, a homogenization annealing step, a milling step, a cold rolling step, a first recrystallization annealing step, an intermediate rolling step, a second recrystallization annealing step, a bottom rolling step, a bottom annealing step, a finished product rolling step, and a stress relief annealing step, wherein the deformation in the intermediate rolling step is 50-70%, and the temperature in the bottom annealing step is 420-450°C.

[0010] Furthermore, the deformation amount in the above-mentioned bottom rolling step is 45-60%, and the holding time in the bottom annealing step is preferably 1-3h. After the bottom annealing step, the average grain size of the strip is preferably <2μm, the grain size standard deviation of the strip is preferably <1.05μm, and the total low ΣCSL grain boundary proportion of the strip is preferably 65-75%; the deformation amount in the finished product rolling step is preferably 25-50%, the temperature in the stress relief annealing step is preferably 260-320°C, and the holding time in the stress relief annealing step is preferably 3-5h. It is preferred that cleaning, finished product straightening and shearing steps are performed after the stress relief annealing step.

[0011] Furthermore, the temperature in the above-mentioned second recrystallization annealing step is controlled at 450-500°C, and the holding time in the second recrystallization annealing step is preferably 3-5h. After the second recrystallization annealing step, the average grain size of the strip is preferably <4μm, the standard deviation of the grain size of the strip is preferably <1.9μm, and the total low ΣCSL grain boundary proportion of the strip is preferably ≥65%.

[0012] Furthermore, the deformation amount in the above-mentioned cold rolling step is 80-90%, the temperature in the first recrystallization annealing step is preferably 520-560° C., and the holding time in the first recrystallization annealing step is preferably 3-6 hours.

[0013] Furthermore, electromagnetic horizontal continuous casting is adopted in the above-mentioned horizontal continuous casting step, and the magnetic field frequency of the electromagnetic horizontal continuous casting is preferably 20-50 Hz, the deformation amount in the pre-rolling step is preferably 7-12%, the temperature in the homogenization annealing step is preferably 650-690°C, and the holding time in the homogenization annealing step is preferably 4-8h.

[0014] By applying the technical solution of the present invention, on the one hand, by controlling the average grain size of the tin-phosphorus bronze alloy strip to be less than 2 μm, and the grains present a uniform normal distribution, and the standard deviation reaches less than 0.9 μm, the grain structure is fine and uniform, and there are no micro-segregation stripes, so that the tin-phosphorus bronze alloy strip can give full play to the effect of fine grain strengthening, and thus a tin-phosphorus bronze alloy strip with high strength, hardness and relatively excellent toughness can be obtained. On the other hand, the tin-phosphorus bronze alloy strip of the present application has the above-mentioned content of large-angle grain boundaries and a higher proportion of total low ΣCSL grain boundaries, especially in the BW direction. It presents a more excellent bending performance, and no defects such as wrinkles appear at a lower R / t value in the BW direction, so that the tin-phosphorus bronze alloy strip can take into account both tensile strength and excellent bending performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0016] Figure 1 A finished product structure photograph of a tin-phosphor bronze alloy strip provided in Example 9 is shown;

[0017] Figure 2 A microstructure photograph of a tin-phosphor bronze alloy strip after bottom annealing provided in Example 9 is shown;

[0018] Figure 3 A distribution diagram of grain size of a tin-phosphor bronze alloy strip after bottom annealing provided in Example 9 is shown;

[0019] Figure 4 A distribution diagram of the finished grain size of a tin-phosphor bronze alloy strip provided in Example 9 is shown;

[0020] Figure 5 The figure shows the proportion of large and small angle grain boundaries in the finished state of a tin-phosphor bronze alloy strip provided in Example 9;

[0021] Figure 6 The figure shows the proportion of total low ΣCSL grain boundaries in the finished state of a tin-phosphorus bronze alloy strip provided in Example 9;

[0022] Figure 7 A finished product structure photograph of a tin-phosphor bronze alloy strip provided in Comparative Example 1 is shown; and

[0023] Figure 8 The figure shows the distribution of the finished grain size of a tin-phosphor bronze alloy strip provided in Comparative Example 1. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0025] As analyzed in the background technology of this application, there is a problem in the prior art that tin-phosphor bronze alloy is difficult to have both high mechanical strength and high bendability. In order to solve this problem, this application provides a tin-phosphor bronze alloy strip and a preparation method thereof.

[0026] In a typical embodiment of the present application, a tin-phosphorus bronze alloy strip is provided, which comprises, by mass percentage, 4.0-10wt% Sn, 0.01-0.3wt% P, and the remainder is Cu and unavoidable impurity elements, the average grain size of the tin-phosphorus bronze alloy strip is less than 2μm, the grains are normally distributed, and the standard deviation is less than 0.9μm; the low ΣCSL grain boundaries in the tin-phosphorus bronze alloy strip account for 10-45% of the entire grain boundaries, the length fraction of the high-angle grain boundaries in the tin-phosphorus bronze alloy strip is 40-85%, and the length fraction of the low-angle grain boundaries is 15-60%.

[0027] Compared with traditional tin-phosphorus bronze, the present invention, on the one hand, controls the average grain size of the tin-phosphorus bronze alloy strip to be less than 2 μm, and the grains present a uniform normal distribution with a standard deviation of less than 0.9 μm, so as to achieve a fine and uniform grain structure without microsegregation stripes, so that the tin-phosphorus bronze alloy strip can give full play to the effect of fine grain strengthening, and thus obtain a tin-phosphorus bronze alloy strip with high strength, hardness and relatively excellent toughness. On the other hand, the tin-phosphorus bronze alloy strip of the present application has the above-mentioned content of large-angle grain boundaries and a higher proportion of total low ΣCSL grain boundaries, especially in the BW direction, it presents a more excellent bending performance, and no defects such as wrinkles appear at a lower R / t value in the BW direction, so that the tin-phosphorus bronze alloy strip can take into account both tensile strength and excellent bending performance.

[0028] Among them, regarding the grain boundary type, a large-angle grain boundary is defined as an orientation difference between adjacent grains greater than 15°, and a small-angle grain boundary is defined as an orientation difference between adjacent grains of 2° to 15°.

[0029] In the CSL model, atoms that overlap at certain positions in crystals with different orientations form a new lattice point, namely the CSL lattice, and its value is expressed by the ratio Σ of the CSL unit cell volume to the crystal lattice unit cell volume. Σ is the density of overlapping positions, which represents the inverse of the ratio of the number of overlapping lattice positions to the total number of lattice positions in the CSL model. The smaller the Σ value, the more overlapping lattice positions there are. Low-Σ grain boundaries are generally called special grain boundaries, that is, CSL grain boundaries with an interface of 3≤Σ≤29. The larger the Σ, the smaller the CSL density. However, when the grain boundary energy is high, the atoms on the overlapping position lattice grain boundaries may not strictly occupy the specified geometric positions, but have a tendency to spontaneously reduce energy, causing the rigid relaxation of the grain boundary atoms, while meeting the Brandon standard. The higher total low-Σ CSL grain boundaries can intercept cracks during bending processing, preventing them from continuing to expand, thereby effectively improving the bending processing performance of the material.

[0030] Since large-angle grain boundaries are more helpful in improving the bending performance of the strip, the length fraction ratio of the large-angle grain boundaries to the length fraction of the small-angle grain boundaries is preferably 1.38-5.67:1, and further, it is preferably any one or more of 1.38-1.86:1, 2.33-2.57:1, and 3.55-5.67:1, so that the strip is less likely to crack at a thinner and smaller bending radius.

[0031] In one embodiment of the present application, the texture components in the above-mentioned tin-phosphorus bronze alloy strip include a Gaussian texture with an area fraction of 3-8%, a copper-type texture with an area fraction of 1-3%, and a brass-type texture with an area fraction of 3-6%, and the texture components are randomly distributed.

[0032] The texture directly affects the performance of the strip, and the preferred texture components are more helpful to balance the bending performance and strength of the tin-phosphorus bronze alloy strip.

[0033] In order to obtain a tin-phosphorus bronze alloy strip having excellent strength while having excellent bending properties, the tensile strength of the tin-phosphorus bronze alloy strip is preferably 610 to 1000 MPa, the yield strength of the tin-phosphorus bronze alloy strip is preferably 580 to 980 MPa, the elongation of the tin-phosphorus bronze alloy strip is preferably 10 to 35%, and the hardness of the tin-phosphorus bronze alloy strip is preferably 200 to 286 HV.

[0034] In one embodiment of the present application, when the tin-phosphor bronze alloy strip is bent at 90°, the R / t value in the GW direction is 0, and the R / t value in the BW direction is ≤0.5. Wherein, the GW direction (good way direction) generally refers to the bending direction in which the bending axis of the specimen collected parallel to the rolling direction is perpendicular to the rolling direction and at right angles. The BW direction (bad way direction) generally refers to the bending direction in which the bending axis of the specimen collected at right angles to the rolling direction is parallel to the rolling direction.

[0035] The above tin-phosphor bronze alloy strips show better bending performance, which is more conducive to meeting the needs of miniaturization and lightweight structural design of connectors.

[0036] In another typical embodiment of the present application, a method for preparing the aforementioned tin-phosphor bronze alloy strip is provided, and the preparation process of the tin-phosphor bronze alloy strip includes a batching step, a horizontal continuous casting step, a pre-rolling step, a homogenization annealing step, a milling step, a cold rolling step, a first recrystallization annealing step, an intermediate rolling step, a second recrystallization annealing step, a bottom rolling step, a bottom annealing step, a finished product rolling step, and a stress relief annealing step, wherein the deformation in the intermediate rolling step is 50-70%, and the temperature in the bottom annealing step is 420-450°C.

[0037] Through the coordinated control of electromagnetic horizontal continuous casting steps, pre-deformation steps of ingots, cold deformation and heat treatment, a finished strip with fine and uniform grain structure and no micro-segregation stripes is obtained, and the high proportion of large-angle grain boundaries and the high proportion of total low ΣCSL of the finished strip are controlled, so as to realize a tin-phosphor bronze alloy strip with high tensile strength and excellent bending performance. Among them, controlling the deformation amount in the intermediate rolling step within the above range helps the above strip to obtain sufficient deformation energy storage, which is enough to provide enough nucleation particles in the subsequent recrystallization annealing process, and through the coordinated control of the temperature in the bottom rolling step and the bottom annealing step (controlling the temperature in the bottom annealing step within the above temperature range, due to the low temperature, the incubation period of recrystallization is long, and a longer time is required to complete the recrystallization, so that the grains are completely recrystallized but not grown, thereby further refining the grain size), it is conducive to further refining the grains, so that the final tin-phosphor bronze alloy strip has both high mechanical strength and high bendability. In one embodiment of the present application, the deformation amount in the above-mentioned bottom rolling step is 45-60%, and the holding time in the bottom annealing step is preferably 1-3h. After the bottom annealing step, the average grain size of the strip is preferably <2μm, the grain size standard deviation of the strip is preferably <1.05μm, and the total low ΣCSL grain boundary proportion of the strip is preferably 65-75%; the deformation amount in the finished product rolling step is preferably 25-50%, the temperature in the stress relief annealing step is preferably 260-320°C, and the holding time in the stress relief annealing step is preferably 3-5h. It is preferred that cleaning, finished product straightening, and shearing steps are performed after the stress relief annealing step.

[0038] Controlling the deformation of the bottom rolling within the above range is conducive to further refinement of the grains. Due to the further refinement of the grains, the deformation energy storage is sufficient under this deformation amount, and enough nucleation particles can be obtained to further refine the strip, and the strip rolling texture is further controlled within a sufficiently low component range, which is still dominated by random texture. On this basis, controlling the temperature and holding time of the bottom annealing has two main purposes: First, within the above temperature range, due to the low temperature, the incubation period of recrystallization is long, and a longer time is required to complete the recrystallization, so that the grains are completely recrystallized but not grown, and the recrystallized grain size can be further refined on the basis of 4μm or less in the previous annealing. The average grain size of the refined organization can be below 2μm, and its standard deviation is controlled below 1.05μm, showing a typical normal distribution, and the grain structure is more uniform and fine. At the same time, the proportion of low ΣCSL grain boundaries in the bottom annealing is controlled to be 65-75%. Lay the foundation for obtaining a high total low ΣCSL grain boundary in the subsequent finished product rolling.

[0039] Since the bottom annealing obtains a relatively fine and uniform grain structure and a higher total low ΣCSL grain boundary, due to the strengthening effect of fine grains, the finished product rolling can obtain the required strength with a smaller deformation of 25-50%. The temperature and holding time of stress relief annealing are controlled within the above range. Since the bottom annealing has a higher proportion of low ΣCSL grain boundaries, a higher proportion of low ΣCSL grain boundaries and a higher proportion of high-angle grain boundaries can still be obtained after the finished product rolling, and the total low ΣCSL grain boundary has a better effect on inhibiting crack propagation. At the same time, according to the Hall-Petch formula and the results of practical experience, under the same deformation amount, fine grains can further improve the tensile strength and hardness of the finished strip, and have better toughness, so that it has higher strength and toughness than ordinary tin-phosphorus bronze. Therefore, the required strength value can be obtained under a smaller deformation amount, and in the stress relief annealing stage, by sacrificing part of the strength or hardness (the strength reduction range is controlled at 25-50MPa, and the hardness reduction range is controlled at 10-30HV), the internal stress of the finished strip is reduced, and the proportion of defects such as dislocations and vacancies is reduced, so that high strength and higher toughness are achieved, thereby reducing the proportion of small-angle grain boundaries and further increasing the proportion of large-angle grain boundaries. The large-angle grain boundaries are more excellent in improving the bending performance of the strip, and are less likely to crack at thinner and smaller bending radii. In addition, the proportion of processed texture in the finished strip is low, and the proportion of random texture is high, so that the strip has excellent bending performance in both the GW direction and the BW direction, thereby making the tin-phosphorus bronze alloy strip have better bending performance while having high tensile strength.

[0040] In one embodiment of the present application, the temperature in the above-mentioned second recrystallization annealing step is controlled at 450-500°C, and the holding time in the second recrystallization annealing step is preferably 3-5h. After the second recrystallization annealing step, the average grain size of the strip is preferably <4μm, the standard deviation of the grain size of the strip is preferably <1.9μm, and the total low ΣCSL grain boundary proportion of the strip is preferably ≥65%.

[0041] After the process of cold rolling and blanking → first recrystallization annealing, a relatively sufficiently refined grain structure has been obtained. At the above-mentioned cold deformation amount of 50-70%, the strip can obtain sufficient deformation storage energy, which is enough to provide enough nucleation particles in the subsequent recrystallization annealing process. Through the coordinated control of the cold deformation amount and the temperature and time of the second recrystallization annealing, it is beneficial to further refine the grains. At this stage, the rolling texture of the intermediate rolling can be controlled within a smaller component range, and the random texture still accounts for the main proportion. After this process, the average grain size of the strip can be controlled below 4μm, the standard deviation is controlled below 1.9μm, the proportion of the total low ΣCLS grain boundary of the strip is more than 65%, the texture in the strip is anisotropic, and each texture component is randomly distributed, laying the foundation for obtaining a high total low ΣCSL grain boundary in the subsequent bottom annealing step.

[0042] In one embodiment of the present application, the deformation amount in the above-mentioned cold rolling step is 80-90%, the temperature in the first recrystallization annealing step is preferably 520-560°C, and the holding time in the first recrystallization annealing step is preferably 3-6h.

[0043] Due to the coordinated control of pre-rolling, homogenization annealing and milling processes, the strip at this time has a relatively fine grain structure and better processing plasticity. On this basis, no cracking of the edge and the strip cracking occurs when cold rolling is carried out under a large deformation of 80-90%. At the same time, due to the large deformation, the partially discrete and uneven recrystallization structure that appears in the homogenization annealing stage is broken more fully, thereby forming more recrystallization nucleation cores, laying the foundation for obtaining a finer grain structure in the subsequent recrystallization annealing process. At the same time, the standard deviation of the grains of the entire strip is smaller, and the distribution of large grains and small grains is normally distributed rather than discretely distributed, which will further improve the bending performance of the finished strip.

[0044] The above-mentioned first recrystallization annealing after cold rolling is not only beneficial to controlling the size of the grains but also helps to control a higher proportion of total low ΣCSL grain boundaries during the first recrystallization annealing. The total low ΣCSL grain boundaries account for more than 65%, and the texture components after annealing are random components, showing anisotropy, thereby avoiding the appearance of a higher proportion of other textures in the subsequent cold rolling process, thereby improving the bending performance of the strip.

[0045] In one embodiment of the present application, electromagnetic horizontal continuous casting is adopted in the above-mentioned horizontal continuous casting step, and the magnetic field frequency of the electromagnetic horizontal continuous casting is preferably 20 to 50 Hz, the deformation amount in the pre-rolling step is preferably 7 to 12%, the temperature in the homogenization annealing step is preferably 650 to 690°C, and the holding time in the homogenization annealing step is preferably 4 to 8 hours.

[0046] The pre-rolling, homogenization annealing and milling (milling removes the surface reverse segregation layer) processes provide good plastic conditions for the ingot. Specifically, electromagnetic assisted casting is applied to suppress the reverse segregation of the tin-bronze ingot, refine the grains, and improve the quality of the ingot. That is, the electromagnetic stirrer body is applied to the crystallization front, and by applying a traveling wave magnetic field, when the electromagnetic stirrer body applies a traveling wave magnetic field above the crystallizer, the melt in the plate and strip will flow under the action of electromagnetic force, making the flow field and temperature field more uniform. At the same time, with the coordinated control of appropriate electromagnetic stirring force and casting process, the solidified dendrites at the crystallization front will be broken and redistributed into the melt, thereby forming more non-heterogeneous effective crystal nuclei and improving the nucleation rate of the tin-phosphorus bronze alloy strip. At the same time, due to the presence of electromagnetic stirring, the heat transfer process of the melt in the crystallizer is also accelerated, making the temperature field of the melt at the front of the solidification interface more uniform, which increases the tendency of the tin-bronze alloy melt to nucleate in large quantities at the same time, thereby improving the uniformity of the outlet temperature of the entire cross-section of the tin-bronze strip, reducing temperature deviation, and reducing the tendency of casting cracking, thereby further improving the quality of the ingot. In addition, it will also accelerate the mass transfer process of the melt in the crystallizer, increase the component supercooling at the front of the solidification interface, and the increase in component supercooling is conducive to the formation and increase of equiaxed crystals, and the grain structure of the tin-bronze ingot is also refined accordingly. Compared with the ingot without electromagnetic assisted casting, there is a phenomenon of coarse grains, columnar grains, and a relatively obvious weak bonding surface in the middle of the slab, and the density of the ingot is low. The present application obtains a tin-phosphor bronze ingot with small reverse segregation of tin elements and dendrite segregation, high density, and refined grain structure in the casting link. Therefore, the high-quality ingot provided by electromagnetic assisted casting can lay the foundation for the subsequent acquisition of tin-phosphor bronze alloy strips with excellent bending performance.

[0047] On the basis of electromagnetic horizontal continuous casting, a certain amount of cold deformation is applied to the ingot after electromagnetic horizontal continuous casting by pre-rolling, and the deformation is controlled at 7-12%. After this step, homogenization annealing is performed. At the same homogenization annealing temperature, the time for the tin bronze to begin recrystallization can be greatly shortened. Combined with Fick's diffusion law, the microsegregation of tin bronze can be eliminated more thoroughly, and the tin element diffuses more evenly during homogenization annealing, and the grain structure is more refined. On this basis, the homogenization annealing time is shortened, greatly reducing energy consumption. The microsegregation in the subsequent finished strip can be greatly reduced, which is conducive to further improving the bending performance of the strip. In particular, on the basis of the above-mentioned pre-deformation of the present application, the above-mentioned homogenization annealing temperature set can make the elements of micro-segregation existing during casting fully diffuse, thereby helping to eliminate the micro-segregation, and within the set holding time, it can ensure that the micro-segregation is basically completely eliminated, while ensuring that the grains are controlled within a reasonable size range, so that the grain size at this stage is controlled within a smaller range, and abnormal growth of grains will not occur, thereby obtaining a relatively fine grain structure, and providing a fine original grain structure for the subsequent tin-phosphor bronze alloy strip to obtain a fine-grained structure.

[0048] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0049] 22 embodiments and 2 comparative examples were selected to prepare tin-phosphor bronze alloy strips according to the preparation method of the present invention. The specific components are shown in Table 1, and the preparation process is: batching → horizontal continuous casting → pre-rolling → homogenization annealing → milling → cold rolling → first recrystallization annealing → intermediate rolling → second recrystallization annealing → bottom rolling → bottom annealing → finished product rolling → stress relief annealing → cleaning → finished product straightening → shearing. The specific process parameter control is shown in Table 2.

[0050] Comparative Examples 1 and 2 were tested on the basis of Example 9, respectively, as shown in Tables 1 to 4 for details.

[0051] Table 1

[0052] Implementation / Comparative Example Content of Sn and P in Tin Phosphor Bronze Alloy Strip Embodiments 1 to 4 4.0wt% Sn, 0.3wt% P Embodiments 5 to 8 6.5wt% Sn, 0.1wt% P Examples 9 to 12, Examples 17 to 22, Comparative Examples 1 and 2 8.0wt% Sn, 0.3wt% P Embodiments 13 to 16 10.0wt% Sn, 0.1wt% P

[0053] Table 2

[0054]

[0055]

[0056]

[0057] Performance testing method:

[0058] Tensile strength: The room temperature tensile test is carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2021 Metallic materials tensile tests Part 1: Room temperature test methods, using a standard dumbbell-shaped specimen for stretching.

[0059] Organization analysis: Grain organization test, using scanning electron microscope EBSD for analysis, the cross-sectional organization (longitudinal section) of the finished sample along the rolling direction is magnified 5000 times for observation. The average grain size and standard deviation of the sample are tested by OIM8.0 analysis software to judge the grain size and grain uniformity distribution of the sample. At the same time, the texture components, texture types, large and small angle grain boundaries, and CSL grain boundaries of tin-phosphor bronze alloy strips can also be analyzed.

[0060] Bending performance: The bending performance test is carried out in accordance with the GB / T 232-010 metal material bending test method by using a HSL-BT-90 bending test machine to perform a 90° bending test. The sample width is 10 mm and the length is 50 mm.

[0061] The specific physical parameters and performance parameters of the tin-phosphorus bronze alloy strips of Examples 1 to 22, Comparative Example 1, and Comparative Example 2 are listed in Tables 3 and 4.

[0062] Table 3

[0063]

[0064] Table 4

[0065]

[0066]

[0067] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0068] Compared with traditional tin-phosphorus bronze, the present invention, on the one hand, controls the average grain size of the tin-phosphorus bronze alloy strip to be less than 2 μm, and the grains present a uniform normal distribution with a standard deviation of less than 0.9 μm, so as to achieve a fine and uniform grain structure without microsegregation stripes, so that the tin-phosphorus bronze alloy strip can give full play to the effect of fine grain strengthening, and thus obtain a tin-phosphorus bronze alloy strip with high strength, hardness and relatively excellent toughness. On the other hand, the tin-phosphorus bronze alloy strip of the present application has the above-mentioned content of large-angle grain boundaries and a higher proportion of total low ΣCSL grain boundaries, especially in the BW direction, it presents a more excellent bending performance, and no defects such as wrinkles appear at a lower R / t value in the BW direction, so that the tin-phosphorus bronze alloy strip can take into account both tensile strength and excellent bending performance.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A tin-phosphor bronze alloy strip, characterized in that: In terms of mass percentage, the tin-phosphor bronze alloy strip comprises: 4.0-10wt% Sn, 0.01-0.3wt% P, and the remainder is Cu and unavoidable impurity elements; the average grain size of the tin-phosphor bronze alloy strip is less than 2μm, the grains are normally distributed, and the standard deviation is less than 0.9μm; the total low ΣCSL grain boundaries in the tin-phosphor bronze alloy strip account for 10-45% of the entire grain boundaries; the length fraction of the high-angle grain boundaries in the tin-phosphor bronze alloy strip is 40-85%, and the length fraction of the low-angle grain boundaries is 15-60%; Wherein, the ratio of the length fraction of the high-angle grain boundary to the length fraction of the low-angle grain boundary is 1.38 to 5.67:1; A low ΣCSL grain boundary is a CSL grain boundary with an interface of 3≤Σ≤29.

2. The tin-phosphor bronze alloy strip according to claim 1, characterized in that: The ratio of the length fraction of the high-angle grain boundary to the length fraction of the low-angle grain boundary is 1.38-1.86:

1.

3. The tin-phosphor bronze alloy strip according to claim 1, characterized in that: The ratio of the length fraction of the high-angle grain boundary to the length fraction of the low-angle grain boundary is 2.33 to 2.57:

1.

4. The tin-phosphor bronze alloy strip according to claim 1, characterized in that: The ratio of the length fraction of the high-angle grain boundary to the length fraction of the low-angle grain boundary is 3.55 to 5.67:

1.

5. The tin-phosphor bronze alloy strip according to claim 1, characterized in that: The texture components in the tin-phosphor bronze alloy strip include: Gaussian texture with an area fraction of 3 to 8%; Copper-type texture with an area fraction of 1 to 3%; Brass-type texture with an area fraction of 3 to 6%; And the texture components are randomly distributed.

6. The tin-phosphor bronze alloy strip according to any one of claims 1 to 5, characterized in that: The tensile strength of the tin-phosphor bronze alloy strip is 610-1000 MPa, the yield strength of the tin-phosphor bronze alloy strip is 580-980 MPa, the elongation of the tin-phosphor bronze alloy strip is 10-35%, and the hardness of the tin-phosphor bronze alloy strip is 200-286 HV.

7. The tin-phosphor bronze alloy strip according to any one of claims 1 to 5, characterized in that: When the tin-phosphor bronze alloy strip is bent at 90°, the R / t value in the GW direction is 0, and the R / t value in the BW direction is ≤0.

5.

8. A method for preparing the tin-phosphor bronze alloy strip according to any one of claims 1 to 7, characterized in that: The preparation process of the tin-phosphorus bronze alloy strip comprises a batching step, a horizontal continuous casting step, a pre-rolling step, a homogenization annealing step, a milling step, a cold rolling step, a first recrystallization annealing step, an intermediate rolling step, a second recrystallization annealing step, a bottom rolling step, a bottom annealing step, a finished product rolling step, and a stress relief annealing step, wherein the deformation in the intermediate rolling step is 50-70%, and the temperature in the bottom annealing step is 420-450°C.

9. The preparation method according to claim 8, characterized in that: The deformation amount in the bottom rolling step is 45-60%, the holding time in the bottom annealing step is 1-3 hours, after the bottom annealing step, the average grain size of the strip is <2μm, the grain size standard deviation of the strip is <1.05μm, and the total low ΣCSL grain boundary proportion of the strip is 65-75%; The deformation amount in the finished product rolling step is 25-50%, the temperature in the stress relief annealing step is 260-320°C, the holding time in the stress relief annealing step is 3-5h, and the steps of cleaning, product straightening and shearing are performed after the stress relief annealing step.

10. The preparation method according to claim 8, characterized in that: The temperature in the second recrystallization annealing step is controlled at 450-500° C., the holding time in the second recrystallization annealing step is 3-5 hours, and after the second recrystallization annealing step, the average grain size of the strip is <4 μm, the grain size standard deviation of the strip is <1.9 μm, and the total low ΣCSL grain boundary proportion of the strip is ≥65%.

11. The preparation method according to claim 8, characterized in that: The deformation amount in the cold rolling step is 80-90%, the temperature in the first recrystallization annealing step is 520-560° C., and the holding time in the first recrystallization annealing step is 3-6 hours.

12. The preparation method according to claim 8, characterized in that: The horizontal continuous casting step adopts electromagnetic horizontal continuous casting, the magnetic field frequency of the electromagnetic horizontal continuous casting is 20-50 Hz, the deformation amount in the pre-rolling step is 7-12%, the temperature in the homogenization annealing step is 650-690°C, and the holding time in the homogenization annealing step is 4-8h.

Citation Information

Patent Citations

  • Tin-phosphor bronze strip with excellent comprehensive performance and preparation method thereof

    CN113106291A